Impact of various parameters on nanostructures fabrication mechanism on silicon surface with AFM tip induced local anodic oxidation. (10th September 2019) - Wang, Xuewen; Theogene, Barayavuga; Mei, Huanhuan; Zhang, Jianwei; Huang, Chenchen; Ren, Xiaoying; Xu, Muxun
Abstract: The AFM tip induced local anodic oxidation (LAO) nanolithography is capable of manufacturing nanometer scale structures and devices for future generation. Experimental studies of LAO on silicon surface, implemented in atmospheric environment by AFM, are presented in this paper. A series of nanostructures with complex patterns was fabricated and analyzed by AFM. The results indicated that various of parameters, such as the applied voltage, pulse time, and ambient humidity, have a strong impact on the height of the nanostructures generated in this way. An advantage of the presented approach is to be utilized in future processing steps in the same environment.